Analysis The Wave Equation Of The Dispersion Term On The Wave Group Velocity - Sumihar Simangunsong (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This study aims to obtain the dispersion equation for the group velocity of waves in a medium. A dispersive medium is a medium in which, when a wave enters the area, the wave undergoes changes in shape and energy. The purpose of this study is to demonstrate how the integral integration method obtains the dispersion equation. This research is qualitative. The location of this research is at the TD Pardede Institute of Science and Technology. From the analysis in this study, it was found that the wave intensity decreases towards the depth of the dispersive medium, assuming that the attenuation coefficient (μ) remains continuous throughout the depth of the material the wave passes through. In the case of seismic waves, when the wave travels through a medium, its intensity decreases with distance. When the absorption coefficient a = 0, the wave is not absorbed but reflected, and when a = 1, the wave is completely absorbed. If a = 0.5, 50 percent of the energy is absorbed. This absorbed energy is converted to heat. In some cases, the absorbed energy can increase the energy of the particles of a substance.